Information and Announcement on the First Global Patient Safety Challenge: Clean Care is Safer Care - Storr, Julie; Allegranzi, Benedetta; Leotsakos, Agnes; Pittet, Didier (International Journal of Infection Control, 2007)
In May 2002, the World Health Assembly passed resolution WHA55.18 which urged countries to pay the greatest possible attention to patient safety. The resolution has ensured that the drive for safer health care is now becoming a worldwide endeavor, bringing significant benefits to patients in countries rich and poor, developed and developing, in all corners of the globe. In October 2004, WHO launched the World Alliance for Patient Safety (WAPS) http://www.who.int/patientsafety/en/. The Alliance is concerned with raising awareness and political commitment in relation to improved patient safety. Each year, the Alliance delivers a number of programmes covering systemic and technical aspects to improve patient safety around the world. The programmes and plans of the Alliance can be found in its Forward Programme 2006-2007: http://www.who.int/patientsafety/information_centre/WHO_EIP_HDS_PSP_2006.1.pdf